Patterns and correlates of polysubstance use among US youth aged 15–17 years: wave 1 of the Population Assessment of Tobacco and Health (PATH) Study - Marushka L. Silveira; Victoria R. Green; Robert Iannaccone; Heather L. Kimmel; Kevin P. Conway (2019)
Youth aged 15-17 years are at high risk of tobacco, alcohol and drug use. Given the changing landscape with respect to availability, use of emerging products and regulatory environments, we examined patterns and correlates of polysubstance use among US youth aged 15-17 years.Cross-sectional self-reported data.United States.A total of 6127 US youth aged 15-17 years from wave 1 (2013-14) of the nationally representative Population Assessment of Tobacco and Health (PATH) Study.Latent class analysis was used to identify subgroups of polysubstance use, including 12 tobacco products, alcohol, marijuana, prescription drugs and other drugs. Socio-demographic characteristics, residence in urban area, sensation-seeking, sexual orientation and internalizing and externalizing problems were examined as correlates.Approximately 43.5% of 15-17-year-olds had used at least one substance in the past 12 months. A 5-class model was identified: class 1 'abstainers' (67.3%), class 2 'alcohol users' (19.2%), class 3 'alcohol, marijuana and tobacco (AMTpredominant AM ) users' (8.2%), class 4 'alcohol, marijuana and tobacco (AMTpredominant T ) users' (3.9%) and class 5 'alcohol, marijuana, tobacco and other drug (AMTOD) users' (1.4%). Abstainers were considered the reference class. Higher sensation-seeking scores, higher age and lower academic grades were each associated with greater likelihood of membership in all user classes. Gender, race/ethnicity, parents/guardians' education, residence in non-urban areas and sexual minority groups were associated with membership in some, but not all, user classes. Compared with no/low/moderate severity, high severity internalizing problems were associated with membership in classes 2, 3 and 5, whereas high severity externalizing problems were associated with membership in classes 3 and 5 only.There appear to be three heterogeneous polysubstance use classes among US youth aged 15-17 years. Correlates of substance use among US youth include higher sensation-seeking, poor academic performance, non-urban residence, minority sexual orientation and mental health problems.